STRUCTURAL PHASE TRANSITION OF PEROVSKITE-LIKE HYBRID MnCl4(C6H5CH2CH2NH3)2 - HIDAYAT (NIM :20515047), ROMEL
Hybrid material is one material that has the potential as the best candidate multiferroic materials. Therefore, many researchers are interested to study and understand the ferroic properties of the hybrid materials, one of which is a ferroelectric properties. In this study examined the role of inorganic and organic moieties in the formation of the state of the ferroelectric properties of twodimensional structure of the hybrid material MnCl4(C6H5CH2CH2NH3)2 (MnClPEA). The study was conducted by investigating structure in the temperature range 100-440 K by using the technique of single crystal X-ray diffraction, whereas the initial identification to determine the phase transition is done by using the technique of differential scanning calorimetry (DSC). MnCl-PEA single crystal is grown through self-assembly reaction with slow evaporation method, using ethanol as a solvent. From DSC thermogram of MnCl-PEA is found in the phase transition temperature are (a) 363 K (T1) and (b) 412 K (T2). The phase transition can be attributed to changes in the structure of the organic and inorganic moieties. MnClPEA structure consists of two-dimensional corner-sharing octahedral of [MnCl6]2- as a part of inorganic and intercalated with two molecules of PEA as organic parts, which are connected by hydrogen bonds. From the results of refinement from single crystal X-ray diffraction data is known that the structure of MnCl-PEA adopt space group Pca21 at temperature below the first transition (T<T1), Abm2 in intermediate phase (T1<T<T2) and Cmca above the second transition (T>T2).